An Introduction to System Biology - Uri Alon (Chapman and Hall/CRC mathematical & computational biology series, 10., 2007)
This book presents recently discovered design principles that govern the structure and behavior of biological networks such as gene circuits, highlighting simple, recurring circuit elements that make up the network. It provides a quantitative theory for which circuits are found in a given environment and a mathematical framework for understanding and even designing biological circuits. The book requires only basic mathematics and includes a review of the necessary background material. It fills a significant need for a textbook and introduction to the concepts, principles, and mathematical tools that will form the basis of future developments in the field